2022
DOI: 10.3390/app12147171
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pectin Branching on the Textural and Swelling Properties of Gel Beads Obtained during Continuous External Gelation Process

Abstract: The aim of the study was to produce gel beads under continuous conditions. Pectins obtained from black and red currants and commercial apple pectin were used as the material. For the production of gel beads, a self-designed device was used. The designed device allows for the production of gel beads in a continuous process, the properties of which are similar to those obtained in the classic, batch process. Thanks to the device, it is possible to obtain a repeatable product while reducing the workload. The prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Michal et al studied the influence of molecular weight and chain linearity in red currant, black currant and apple pectin. The findings of the study reflected that the black currant pectin with lower molecular weight and highly branched polymer chain had lower gel strength 52 . Wang et al, reported in their study that both apple pectin and citrus pectin decreased in viscosity with increase in shear rate, which is caused by the random coil of pectin polysaccharides 53 .…”
Section: Pectin‐source Structure and Film Forming Characteristicsmentioning
confidence: 67%
See 1 more Smart Citation
“…Michal et al studied the influence of molecular weight and chain linearity in red currant, black currant and apple pectin. The findings of the study reflected that the black currant pectin with lower molecular weight and highly branched polymer chain had lower gel strength 52 . Wang et al, reported in their study that both apple pectin and citrus pectin decreased in viscosity with increase in shear rate, which is caused by the random coil of pectin polysaccharides 53 .…”
Section: Pectin‐source Structure and Film Forming Characteristicsmentioning
confidence: 67%
“…The findings of the study reflected that the black currant pectin with lower molecular weight and highly branched polymer chain had lower gel strength. 52 Wang et al, reported in their study that both apple pectin and citrus pectin decreased in viscosity with increase in shear rate, which is caused by the random coil of pectin polysaccharides. 53 When subjected to shear force, pectin with a lower molecular weight (Mw) experiences a more rapid decrease in viscosity because of its shorter chains and weaker inter-or intra-molecular interactions.…”
Section: Exploring the Attributes Of Pectin And Their Impact On Film ...mentioning
confidence: 97%
“…Differences in the water absorption capacity of PEC are related to the molecular structure. SR is mainly influenced by the degree of esterification-when the degree of esterification is smaller, PEC has a greater capacity to absorb water [10]. It was shown that the crosslinked formulations were characterized by a higher SR (from 1.33 ± 0.48 in formulation P1 to 11.05 ± 0.92 in formulation P6 after 120 min).…”
Section: Swelling and Erosionmentioning
confidence: 99%
“…Accurately weighted films in the baskets (accessories from USP dissolution equipment) were situated in the beakers containing 15 mL SSS. Studies were conducted at the temperature of 37 ± 1 • C and at different time periods (5,10,15,30,45,60, 90 and 120 min). After a certain time, the baskets were taken out of the beakers and cautiously strained.…”
Section: Swelling Propertiesmentioning
confidence: 99%
See 1 more Smart Citation